Flowering ground vegetation benefits wild pollinators and fruit set of almond within arid smallholder orchards - Norfolk, Olivia; Eichhorn, Markus P.; Gilbert, Francis (Wiley, 2016)
Pollination studies tend to focus on the conventional agriculture associated with Europe and the USA, leaving a gap in our understanding of how pollination services are maintained in smallholder agricultural systems that dominate much of the developing world. In South Sinai, Egypt, almond is cultivated as part of an arid agroforestry system in traditional orchard gardens that contain a mixture of fruit trees inter-planted with vegetables and herbs. This study investigated the relative contribution of honeybees and wild insects for pollination of almond trees and assessed how flowering ground vegetation influenced pollinator densities and fruit set. Results showed that almond was highly dependent on insect pollination, with bagged flowers producing less than 8% of the fruit set of insect- and hand-pollinated flowers. Fruit set was correlated with wild pollinator visitation, but not with honeybee visitation. Furthermore, the presence of honeybee hives had no effect upon fruit set. The abundance and species richness of flowering ground vegetation was positively related to pollinator abundance within the gardens and associated with enhanced fruit set. Over half of the flowering ground flora were minority crops grown alongside almond, suggesting that facilitation can occur between simultaneously flowering crops. In these diverse orchard gardens, flowering minority crops benefited wild pollinators and increased fruit set in the primary orchard crop. If mutual facilitation occurs between other crop species, then the diverse cropping systems associated with smallholder farms are likely to enhance pollination services within traditional agricultural landscapes.